2022
DOI: 10.3389/fcell.2022.811701
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Autophagy Enhancers in Metabolic Disorders and Other Diseases

Abstract: Autophagy is pivotal in the maintenance of organelle function and intracellular nutrient balance. Besides the role of autophagy in the homeostasis and physiology of the individual tissues and whole organism in vivo, dysregulated autophagy has been incriminated in the pathogenesis of a variety of diseases including metabolic diseases, neurodegenerative diseases, cardiovascular diseases, inflammatory or immunological disorders, cancer and aging. Search for autophagy modulators has been widely conducted to amend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 244 publications
(276 reference statements)
1
8
0
Order By: Relevance
“…[93][94][95][96][97][98] Thus, the suppression of hyperactive mTORC1 by TZDs may account for their apparent insulin-sensitising activity, resulting in glycaemic control while suppressing insulin secretion. Also, the suppression of hyperactive mTORC1 by TZDs may drive cardio-renal and beta-cell autophagy and mitophagy, 99 thereby counteracting diabetic cardiomyopathy, nephropathy and beta-cell failure. Also, the suppression of hyperactive mTORC1 by TZDs may account for their pleiotropic activities beyond the diabetic context, resulting in alleviating hepatic steatosis, blood pressure, dyslipidemia, inflammatory biomarkers, endothelial damage, a variety of cancer types, neurodegeneration and ageing.…”
Section: Pparg Activation By Tzds Results In Transcriptional Activati...mentioning
confidence: 99%
“…[93][94][95][96][97][98] Thus, the suppression of hyperactive mTORC1 by TZDs may account for their apparent insulin-sensitising activity, resulting in glycaemic control while suppressing insulin secretion. Also, the suppression of hyperactive mTORC1 by TZDs may drive cardio-renal and beta-cell autophagy and mitophagy, 99 thereby counteracting diabetic cardiomyopathy, nephropathy and beta-cell failure. Also, the suppression of hyperactive mTORC1 by TZDs may account for their pleiotropic activities beyond the diabetic context, resulting in alleviating hepatic steatosis, blood pressure, dyslipidemia, inflammatory biomarkers, endothelial damage, a variety of cancer types, neurodegeneration and ageing.…”
Section: Pparg Activation By Tzds Results In Transcriptional Activati...mentioning
confidence: 99%
“…Several groups have developed such autophagy modulators, and studied the effects of novel agents or known drugs, such as berberine, imatinib, MSL‐7, rapamycin, resveratrol, spermidine, trehalose, rosiglitazone or fenofibrate, on β‐cell autophagy and diabetes. Readers are encouraged to consult recent reviews 69 . In the present review, the role of autophagy in the effects of known drugs that are already used for treating metabolic disorders and diabetes is discussed.…”
Section: Antidiabetic Drugs and β‐Cell Autophagymentioning
confidence: 99%
“…Since autophagy controls intracellular nutrient homeostasis and the integrity of organelles that are critical for energy balances, dysregulation of autophagy is likely to contribute to the pathogenesis of metabolic disorders. Hence, changes of autophagy in metabolic tissues have been extensively studied in metabolic diseases 37 , 38 . Previous studies have reported that autophagy can protect pancreatic β-cells against metabolic stress, such as palmitic acid (PA)-induced lipotoxicity, in vitro 39 , 40 .…”
Section: Autophagy Of Pancreatic β-Cellsmentioning
confidence: 99%